(3TQM bUjOI GdHQOI ddHhUjQis - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s; (3eMeO Hf SYjO Hf MeGO GdUfgGLj GdHhUjQj, (B696 (3g`,J (B696 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO ddg eSJMb GdMeO hGdJgdjd hGdJcHjQ hGdJSHjM , GdUdGg hGdSdGe Ydi SjOfG eMeO UGMH GdhLg GdedjM s
(3BNQgG (B:s
(3aeG JaQb Hjf GdHge hGdHge hQHi LeY QHhg HVe GdQGA haJMgG hcSQgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3CHjGJ GdbUjOI eTchdIs
(3GdeGOI ecJhHI Ydi YehOjfs
(3ai BNQ UaMGJgG JYbjHIs
(3fSNI KGfjI GdTQM GdeNJUQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B11s
Keywords: (3GdCOHs